An adjusted ELISpot-based immunoassay for evaluation of SARS-CoV-2-specific T-cell responses - Hao Lin; Jie Zhang; Shaobo Dong; Yaning Liu; Peipei Liu; George F. Gao; William J. Liu; Guizhen Wu (Elsevier, 2022)
Like antibody evaluation, using an effective antigen-specific T-cell immunity assessment method in coronavirus disease 2019 (COVID-19) patients, survivors and vaccinees is crucial for understanding the immune persistence, prognosis assessment, and vaccine development for COVID-19. This study evaluated an empirically adjusted enzyme-linked immunospot assay for detecting severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-specific T-cell immunity in 175 peripheral blood samples from COVID-19 convalescents and healthy individuals. Results of viral nucleic acid were used as the gold standard of infection confirmation. The SARS-CoV-2M peptide pool had higher sensitivity of 85% and specificity of 71% for the single peptide pool. For combined peptide pools, the parallel evaluation (at least one of the peptide pools is positive) of total peptide pools (S1&S2&M&N) had higher sensitivity (up to 93%), and the serial evaluation (all peptide pools are positive) of total peptide pools had higher specificity (up to 100%). The result of the serial evaluation was better than that of the parallel evaluation as a whole. The detection efficiency of M and N peptide pool serial evaluation appeared the highest, with a sensitivity of 80% and specificity of 93%. This T-cell immunity detection assay introduced in this report can achieve high operability and applicability. Therefore, it can be an effective SARS-CoV-2-specific cellular immune function evaluation method.